PREP TION OF EXTRUDER EXTRUDED FISH SNACK USING TWIN SCREW STO GEC CTERISTICS OF THE PRODUCT - Basu, S.; Sharma, Shiv Kumar (Journal of Indian Fisheries Association, 2015)
A value-added extruded fish product was prepared with corn flour (80%)and fish (sciaenid) powder (20%), using a twin-screw extruder. The effect ofdifferent parameters like moisture, temperature, fish powder concentration,speed of the extruder and die-diameter on expansion ratio and crisp texturewere studied. The storage characteristics of the final product were studiedusing three different types of packaging under nitrogen flushing. The studyrevealed that aluminium foil is the best packaging material to keep theproduct acceptable for more than three months.Key words: Extruded fish product, twin-screw extruder, storagecharacteristics